PERAN FILSAFAT DALAM DUNIA PENDIDIKAN NASIONAL - Suhari Suhari (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyse the role of philosophy in national education as a fundamental basis for formulating objectives, curricula, learning methods, and nation-building. Indonesian national education cannot be separated from the values of Pancasila as the foundation of the state, which serves as the philosophical basis for the implementation of education. This foundation is confirmed in Law No. 20 of 2003 concerning the National Education System, which emphasises the holistic development of students' potential, including spiritual, intellectual, moral, and social aspects. This study uses a qualitative approach with a library research type. Data was obtained through a review of laws and regulations, books, and scientific journals relevant to the philosophy of education, including the thoughts of Ki Hajar Dewantara as a national education figure. The data analysis technique used content analysis to identify the main concepts and their relationship with the national education system. The results of the study show that philosophy plays a normative and conceptual role in determining the direction of national education, shaping the character of students, and serving as a guideline in facing the challenges of globalisation. Thus, strengthening the philosophical foundation of education is important so that the national education system remains rooted in national values and relevant to the times.